Hemoparasitism in grazing cattle and risk factors associated with husbandry management in an endemic area of Eastern Colombia (2024)
Vector-borne pathogens induce hemoparasitism in cattle causing substantial economic losses in tropical and subtropical areas. Infectious cattle actively contribute to maintaining the transmission cycle, and the presence of these animals must be associated with husbandry management and environmental changes. In the present study, we conducted a cross-sectional study sampling 1,000 bovines to identify infectious cattle diagnosed by a direct technique and employed a dichotomic questionnaire for association analyses, hierarchical clustering, and Principal Component Analysis (PCA). Overall prevalence with infectious cattle was 34.99%, where 97% of the farms had at least one infectious animal per genera, and the prevalence in properties ranged between 16.39 and 53.85%. Of these animals, 26.20% tested positive for Anaplasma sp., 8.40% for Babesia spp., and 1.30% for Trypanosome spp. The main co-infection showed 5% Anaplasma sp. – Trypanosome spp., followed by 4% Babesia spp. – Trypanosome spp. These bovines showed association with the use of the Jersey breed (OR = 2.016 C.I:1.188–3.419), selling animals for replacement (OR = 1.417 CI:1.022–1.965), participation in livestock exhibitions (OR = 2.009 CI:1.262–3.199), premises with burials (OR = 2,064 CR: 1.414–3.011), use of palm kernel (OR = 1.935 C.I:1.198–3.124), and the use of ivermectin (OR = 1.548 CI: 1.085–2.210) as a susceptibility. The hierarchical clustering revealed clusters among properties with different hemoparasite prevalence, with notable co-infections observed. The subsequent PCA identified that significant risk factors contributed to hemoparasitism positivity. We conclude that infectious cattle in the endemic area showed an association with husbandry management that permits the success of vector and maintenance of the enzootic or epizootic cycle in the herds.